2019
DOI: 10.1002/lt.25448
|View full text |Cite
|
Sign up to set email alerts
|

Underestimation of Liver Transplantation for Alcoholic Hepatitis in the National Transplant Database

Abstract: Alcohol‐associated liver disease (ALD) can be coded in United Network for Organ Sharing (UNOS) as either alcoholic cirrhosis or alcoholic hepatitis (AH), without having specific criteria to assign either diagnosis. In this multicenter American Consortium of Early Liver Transplantation for Alcoholic Hepatitis (ACCELERATE‐AH) study, we sought to assess the concordance of the clinician diagnosis of AH at liver transplantation (LT) listing versus UNOS data entry of AH as listing diagnosis. In a prior study, consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 12 publications
0
37
0
2
Order By: Relevance
“…These results suggest that AH patients might have better waitlist outcomes than chronically debilitated patients in cases of their waitlist time being over 90 days. Hence, it will be essential to continually assess disease progression in patients with AH to stratify prognosis 5,18‐22 . Conversely, we found AH patients with coagulopathy and those who required life support had a significantly higher risk of waitlist mortality.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…These results suggest that AH patients might have better waitlist outcomes than chronically debilitated patients in cases of their waitlist time being over 90 days. Hence, it will be essential to continually assess disease progression in patients with AH to stratify prognosis 5,18‐22 . Conversely, we found AH patients with coagulopathy and those who required life support had a significantly higher risk of waitlist mortality.…”
Section: Discussionmentioning
confidence: 77%
“…The diagnosis of AH may be misclassified or underestimated in the UNOS registry. It was recently reported that some patients with AH are incorrectly listed with the diagnosis code of “alcoholic cirrhosis” or “acute liver failure.” 22 We included only patients coded as AH and excluded patients with overlapping diagnoses, which should help homogenize the AH cohort in this study. However, it should be acknowledged that small changes in the number of patients with AH could lead to outsized statistical impact.…”
Section: Discussionmentioning
confidence: 99%
“…Results published by Mathurin et al 3 and subsequent studies conducted by the American Consortium of Early Liver Transplantation for Alcoholic Hepatitis (ACCELERATE-AH) 8 - 11 , 15 have paved the way for considering LT for AH patients. Investigators with ACCELERATE-AH, a multicenter observational study describing outcomes of early LT in patients with severe AH, noted a slight increase in frequency of LTs for the management of AH in the United States in 2016.…”
Section: Discussionmentioning
confidence: 99%
“… 3 The requirement for a 6-month abstinence period before LT has been challenged due to lack of data supporting it. 4 - 7 The case for LT in severe AH is further strengthened by studies conducted by US consortium; these studies have reiterated the improved survival following LT for AH, with a score created to predict the likelihood of relapse post LT. 8 - 11 …”
Section: Introductionmentioning
confidence: 99%
“…18 These surveys mirror published single center and cohort data 19 along with national registry data from United States showing an increase in the number of liver transplants for severe AAH performed from 2012 to 2017. 20 Additionally, since the landmark study by Mathurin et al in 2011, practice in France regarding early liver transplantation for severe AAH has changed. In 2018, a survey conducted among 18 French transplant centers showed that prior to 2011, 35% of centers did not perform liver transplantation for AAH.…”
Section: Current Practice: 6-month Rulementioning
confidence: 99%